Development of an anthropomorphic arm for manipulation - Teixeira, Bruno Daniel Almeida (2017)
Nowadays, service robots are used for private or research usage, like in space programs to explore planets, or in an University project. This dissertation is mainly focused on the development of an anthropomorphic arm and its assemble on the platform CAMBADA@Home to participate and achieve better results in the RoboCup competition. In this dissertation it will be explained how the robotic arm for CAMBADA@Home was developed. This will include the motors used, BLDC motor and Dynamixel servo motors, as well as the construction of a model of the arm with the use of a CAD software, which involves the use of the motors designed and the creation of some parts to connect them, as well as the assembly of the physical model. Afterwards the hardware and software control were developed. It was also used a simulator in order to safely test the model. Then a few test were run which consisted on the use of no load an with a load of 263 grams. Additional test were run to verify if the planning sequence matched the physical trajectory